Determinants Related to SIM-RS user Satisfaction - Denny Herry Wardhana; Sumijatun Sumijatun; Ali Germas Kodyat (Indonesian Journal of Global Health Research, 2025)
Based on initial observations, there are still complaints from users regarding the slow system, difficulty in data input, and the suboptimal function of SIM-RS in supporting services at Bhayangkara Level III Hospital, Banda Aceh. The purpose of this study was to determine the determinants related to SIM-RS user satisfaction at Bhayangkara Level III Hospital, Banda Aceh. Quantitative research was used with a cross-sectional study design. The sample consisted of 91 health workers using the total sampling method. Data collection used instruments. The results showed that partially there was a significant relationship between system quality (p = 0.0001), information quality (p = 0.015), and service quality (p = 0.0001) of SIM-RS with SIM-RS user satisfaction at Bhayangkara Level III Hospital, Banda Aceh. Logistic regression analysis showed that SIM-RS System Quality (P = 0.0001) and SIM-RS Service Quality (P = 0.001) were significant predictors related to SIM-RS user satisfaction at Bhayangkara Level III Hospital, Banda Aceh. Conclusions: The results of the study indicate that the SIM-RS System Quality factor is the most significant predictor related to satisfaction with SIM-RS use at Bhayangkara Hospital Level III Banda Aceh (OR: 39.738).